2020
DOI: 10.1371/journal.pone.0238495
|View full text |Cite
|
Sign up to set email alerts
|

Changing prevalence and factors associated with female genital mutilation in Ethiopia: Data from the 2000, 2005 and 2016 national demographic health surveys

Abstract: Setting Female genital mutilation (FGM) is a traditional surgical modification of the female genitalia comprising all procedures involving partial or total removal of the external female genitalia or other injury to the female genital organs for cultural or nontherapeutic reasons. It can be harmful and violates girls' and women's human rights. FGM is a worldwide problem but mainly practiced in Africa. FGM is still widely practiced in Ethiopia despite being made a criminal offence in 2004. Objective Using data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
(42 reference statements)
2
0
1
Order By: Relevance
“…Religion of the parents was another factor in luencing daughter's circumcision, where only 2% of Christians circumcised their daughters. This inding is consistent with the study conducted in Upper Egypt [19] and Burkina Faso [26]. There were no signi icant association between maternal occupation and FGM.…”
Section: Discussionsupporting
confidence: 92%
“…Religion of the parents was another factor in luencing daughter's circumcision, where only 2% of Christians circumcised their daughters. This inding is consistent with the study conducted in Upper Egypt [19] and Burkina Faso [26]. There were no signi icant association between maternal occupation and FGM.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, this underscores the need to design health education programs and conduct information, education, and communication interventions among mothers on FGC, especially on its negative health implications. This finding was similar to studies conducted in Iran [ 38 ], Sierra Leone [ 37 ], Nigeria [ 35 ], and Ethiopia [ 19 , 47 ], which showed that women’s intention not to perform FGC on daughters increases with their educational level. We also found that the age of the respondents predicted their intention to experience FGC.…”
Section: Discussionsupporting
confidence: 89%
“…However, more awareness programmes to deter the practice of FGM/C are still needed to further reduce the prevalence. The prevalence of FGM/C among the youngest daughters in this study was higher than those reported in the UAE [ 34 ], Ethiopia [ 36 ], and Sudan [ 37 ]. As abovementioned, we postulated that the differences in the prevalence were attributed to the different study populations, i.e.…”
Section: Discussioncontrasting
confidence: 80%